Compensation /George T. Milkovich, Jerry M. Newman, Barry Gerhart - Milkovich, George T.
Tackles major compensation from three sides: theory, research, and practice. This edition continues to emphasize the importance of total compensation and its relevance for achieving sustainable competitive advantage. It also conducts executive seminars in many countries and served on advisory boards of leading academic/research centers.